Bulk Deposition and Source Apportionment of Atmospheric Heavy Metals and Metalloids in Agricultural Areas of Rural Beijing during 2016–2020 - Yuepeng Pan; Jin Liu; Lan Zhang; Jing Cao; Jiabao Hu; Shili Tian; Xingyu Li; Wen Xu (Atmosphere, 2021)
While atmospheric deposition plays a vital role in cleaning air pollutants, it also supplies toxic heavy metals and metalloids (MMs) to the receiving terrestrial and aquatic ecosystems and threatens human health through food chains. To characterize the input of atmospheric deposition to agricultural soils, bulk rain samples were collected on an event basis at a rural site in the North China Plain during 2016–2020. The results show that higher concentrations of MMs in bulk rain samples were associated with western and southern air masses passing polluted areas. In addition, the annual deposition flux of MMs tends to decline during the study period, coinciding with the inter-annual variations of particulate matter rather than the precipitation amounts. Of note, the deposition flux of MMs that exist entirely in fine particles declined significantly compared to those that exist in coarse particulate form, indicating that the clean air actions implemented in recent years were highly effective in reducing ambient MMs from anthropogenic emissions. The positive matrix factorization receptor model was also applied to the whole data set for bulk depositions and five sources were identified as agricultural (biomass burning and soil), dust, coal combustion, industrial and traffic emissions. These factors contributed 41%, 24%, 21%, 9% and 5% of the chemical components in bulk depositions, respectively. Future control strategies should tighten the emissions from combustion and soil/dust in the North China Plain to protect agriculture from atmospheric MMs depositions.